Relationship between the duration of diabetes and severity of neuropathy in patients of peripheral neuropathic diabetic foot ulcers - Kumar, Utkarsh; Singh, Anjali; Singla, Deepak; Agrawal, Nivesh (International Journal of Research in Medical Sciences, 2023)
Background: Diabetic foot ulcer (DFU) has devastating impact on the social, personal as well as economic life of a diabetic patient. In US, prevalence of peripheral neuropathy in adult diabetics is approximately 28%. The aim of this study is to establish relationship between the duration of diabetes and severity of neuropathy in patients with peripheral neuropathic DFU. Methods: This is a prospective observational study, including 30 patients, who underwent history, examination and Toronto clinical scoring system (TCSS) was used for diagnosing severity of diabetic peripheral neuropathy (mild, moderate, severe) from a period of October 2015 to June 2017. Results: In this study, we observed that the mean age of the diabetic foot patients was 53.50±12.03 years ranging from 30 to 75 years. Male-to-female ratio was 1.5:1. The mean duration of diabetes was 6.38±4.57 years. The patients with mild neuropathy had a mean duration of diabetes of 4.77±2.61 years, while, those with moderate and severe neuropathy had mean duration of 7.17±1.48years and 8.48±4.59 years, respectively. Conclusions: The study concluded that there is a significant association between duration of diabetes and severity of neuropathy, i.e., patients with longer duration of diabetes had severe peripheral neuropathy.